Análisis del proceso de cultivo y rehabilitación de cacao en un resguardo indígena para implementar los principios de biocomercio (2014)
The article gathered the principal factors studied and evaluated by the author to analyze the cocoa production process carried out by the indigenous of Motilón-Barí indigenous reservation, in light of the seven principles of Bio Trade, aimed at helping this communities with conservation practices and sustainable use in their agricultural practices. Each of the seven principles was studied, identifying the way used to promote the biodiversity conservation through its sustainable commercial use and assessing the contribution to obtain food and incomes for the small producers located at that poverty area.